Before Copernicus and Copernicus - Vesel, Matjaž (Aestimatio, 2020)
A discussion of Before Copernicus: The Cultures and Contexts of Scientific Learning in the Fifteenth Century edited by Rivka Feldhay and F. Jamil Ragep.